Productivity, technical efficiency, and farm size in Paraguayan agriculture - Thomas Masterson (Levy Economics Institute of Bard College, 2007)
This essay assesses the relationship between farm size and productivity. Both parametric and nonparametric methods are used to derive efficiency measures. Smaller farms are found to have higher net farm income per hectare, and to be more technically efficient, than larger farms.
Keywords: Q12; O12; 330; Farm Size; Productivity; Technical Efficency; Paraguay